Mapping cell behavior across a wide range of vertical silicon nanocolumn densities - Buch-Manson, Nina; Kang, Dong-Hee; Kim, Dongyoon; Lee, Kyung Eun; Yoon, Myung-Han; Martinez, Karen L. (ROYAL SOC CHEMISTRY, 2017)
Over the past decade, vertical nanostructures have provided novel approaches for biomedical applications such as intracellular delivery/detection, specific cell capture, membrane potential measurement, and cellular activity regulation. Although the feasibility of the vertical nanostructures as a new biological tool has been thoroughly demonstrated, a better understanding of cell behavior on vertical nanostructures, in particular the effects of geometry, is essential for advanced applications. To investigate the cell behavior according to the variation of the spacing between vertical nanostructures, we have interfaced fibroblasts (NIH3T3) with density-controlled vertical silicon nanocolumn arrays (vSNAs). Over a wide range of vSNA densities, we observe three distinct cell settling regimes and investigate both overall cell behavior (adhesions, morphology, and mobility) and detailed biomacromolecule variance (F-actin and focal adhesion) across these regimes. We expect that these systematic observations could serve as a guide for improved nanostructure array design for the desired cell manipulation.
Keywords: NANOWIRE ARRAYS; LIVING CELLS; EFFICIENT CAPTURE; ENZYMATIC-ACTIVITY; MEDIATED DELIVERY; FOCAL ADHESION; T-LYMPHOCYTES; STEM-CELLS; DIFFERENTIATION; NANONEEDLES